The role of non-performing loans for bank lending rates - Sebastian Bredl (Deutsche Bundesbank, 2018)
Against the backdrop of a high stock of non-performing loans (NPLs) in several European countries, this paper investigates the role of NPLs for lending rates charged for newly granted loans in the euro area. More precisely, it looks for an effect that extends beyond losses caused by that stock which have already been incorporated into the banks' capital positions. The paper focuses on the question of which channels are responsible for such a potential effect. The results indicate that a higher stock of net NPLs is associated with higher lending rates, whereby there are indications that this relation tends to be offset by loan loss reserves. Although the NPL stock affects banks' idiosyncratic funding costs as well, the latter do not seem to constitute an important link between the stock of NPLs and lending behavior. Furthermore, NPLs do not strongly affect the banks' interest rate pass-through.
Keywords: G21; E43; 330; lending rates; non-performing loans; impaired loans; funding costs